"Prisons Were Made for People Like Us": British Pakistani Muslim Experiences Upon Release From Prison. (June 2020) - Qasim, Mohammed; Webster, Colin
British Muslim young men who offend upon reentry from prison reported that "Prisons were made for people like us." At one level, this meant that the challenges they faced were likely to be intractable and insurmountable, regrettably returning them to prison. At another, their social integration after release from prison was hampered by something more than their individual choices and agency. Cycling between neighborhood, offending, and prison, it was their characteristic social relations and the peculiar social structural constraints placed upon them as a group that best explained their experiences upon release from prison.